ENT 530 : Case Study: Inaiscarves / Nur Afiqah Mansor ... [et al.] - Mansor, Nur Afiqah; Saipuddin, Norsyafi Imanina; Mohamad Ariffin, Nur Asyiqin; Zuraimi, Miza Izzati; Md Yazid, Nur Syafiqah (2021)
The case study is focusing on analysing and researching the small business or company regarding their main problem they encounter and proposed a solution pertaining to the analysed problem. It also focuses on the information gathering regarding the business in terms of background, products, marketing strategies and SWOT analysis. The company that we have chosen is Inaiscarves which is a local scarves brand in Malaysia that has been serving the business industry. Inaiscarves is a specialist in producing ‘Bawal’ type of scarves with detailed designs and high-quality materials. In early 2021, they launched their first Set Casual Suits for women in the market. This brand was founded on 4 th August 2016, with the dedication and passionate husband and wife, Mr Muhamad Zul Fathi’ i Bin Zakaria and Puan Mrs Siti Nurzarifah binti Nurman Shah. They are very active in promoting, selling their products online by their own social media platforms such as official website, Instagram, Facebook. Now, they are reaching five years in this business industry, still serving their best quality products.